THE USE OF BLOCKCHAINS. AN R APPROACH - Nicolae-Marius JULA; Nicoleta JULA (Challenges of the Knowledge Society)
The cryptocurrency is a hot topic and understanding the blockchain is very important. Also, understanding what blockchain may lead to more decentralized services and applications to be used, not only in relation to financial applications. Today, blockchains can be used to for smart contracts, decentralized networks, governments and non-profit organizations, banks and even photography copyright recordings and smart contracts for music artists. Even World Economic Forum predicted that by 2015 about 10% of global GDP will be stored on blockchain technology. The blockchain technology cosists in creating a chain of blocks, validated with a hash function and under a “proof of work” concept, which limits speed of creating new blocks. The new technology is open source, but recently has attracted the attention of big software players, like Microsoft and other companies (BBVA, UBS). In this paper, we present a simple R implementation of a blockchain, containing a initial block, creation of each blocks (including hash and proof of work) and the creation of the chain. Data validation and the lack of so-called middle man, minimization of the fees, increasing the speed of transactions, security and anonymity provided by this technology are good arguments for ensuring the continuous development of the technology and its spreading in everyday activities.